1986
DOI: 10.1111/j.1528-1157.1986.tb03539.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Arteriovenous Malformations and Epilepsy: Factors in the Development of Epilepsy

Abstract: Sixty-one patients of a population of 343 with cerebral arteriovenous malformations (AVMs) were diagnosed with seizures. Their AVMs were larger (p less than 0.02) and more frequently superficial (p less than 0.05) as compared with the AVMs of patients who were diagnosed with haemorrhage. The factors influencing the development of denovo seizures in patients with diagnosed AVMs were surgical treatment, a presentation with haemorrhage, and age at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 5 publications
4
51
2
3
Order By: Relevance
“…Luhdorf et al [1986] report that the dominant cause of epilepsy in patients over 60 years is cerebrovascular disease, and oc currence of the seizures during the 1st week following stroke is a poor prognostic indica tor with higher mortality. Crawford et al [1986] observed that epilepsy results more commonly following hemorrhage, or with large enlarging arteriovenous malformations with superficial components, and following surgery for these malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Luhdorf et al [1986] report that the dominant cause of epilepsy in patients over 60 years is cerebrovascular disease, and oc currence of the seizures during the 1st week following stroke is a poor prognostic indica tor with higher mortality. Crawford et al [1986] observed that epilepsy results more commonly following hemorrhage, or with large enlarging arteriovenous malformations with superficial components, and following surgery for these malformations.…”
Section: Discussionmentioning
confidence: 99%
“…IVMs and their associated aneurysms pose important but variable risks of sometimes recurrent intracranial hemorrhage and epilepsy, potentially leaving people with long-term disability and handicap. [2][3][4][5][6][7][8] Despite the importance of IVMs, there are few high-quality studies of their frequency, prognosis, and treatment. 9,10 Ideally, accurate estimates of detection should be based on complete, prospective ascertainment from a well-defined, stable population or a representative sample of one.…”
mentioning
confidence: 99%
“…28,29 Only 1 observational study compared the risk of de novo seizures following AVM surgery to the risk during conservative management, finding that the risk was greater following surgery, but the study was retrospective and based on clinical practice between 1941 and 1984. 30 There have been no randomized controlled trials to compare seizure outcomes following AVM treatment vs conservative management. 31 Therefore, we conducted a prospective, population-based, observational cohort study and analyzed it to compare the risk of a first seizure, the risk of epilepsy, and the chances of achieving 2-year seizure freedom, for adults undergoing AVM treatment or conservative management.…”
mentioning
confidence: 99%